Facetas del vínculo literario de José María Arguedas y Javier Sologuren: epifanías y otras concordancias en «Los ríos profundos» (1958) y «Estancias» (1960) - Guizado-Yampi, Renato (2024)
Little has been written about the literary link that was established between the narrator José María Arguedas and the poet Javier Sologuren, two of the most relevant Peruvian writers of Latin American literature of the 20th century. Beyond the friendship and the editorial anecdote, the thought and work of Arguedas influenced the ideas of Sologuren about the national literary tradition in which his work was inscribed. This article investigates more concrete traces of this nexus. First, it examinates the peculiar interpretation that Sologuren established of an Arguedas who was a poet and then a narrator. From this, it analyzes the thematic and formal parallels between the novel Los ríos profundos (1958) and the collection of poems Estancias (1960), dedicated to Arguedas. As will be seen, there are some interesant coincidences, and in both works the literary epiphany is important, because it reveals a higher reality.